PENGARUH KOMUNIKASI INTERPERSONAL TERHADAP KINERJA KARYAWAN DI DAIMA HOTEL PADANG - Eldia, Shinta Putri; Kasmita, Kasmita; Suyuthie, Hijriyantomi (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2017)
This reseach aims to find out how big the influence of interpersonal communication (X) on employee performance (Y) in Daima Hotel Padang, with total populations of 74 employees and Sample with 43 permanent employees. Data collection techniques were conducted by using questionnaires, and documentation by using Likert scale that has been tested for its validity and reliability. Further data is analyzed through description and correlation analysis with the help of computer program SPSS version 16.00. The results of this reseach found that: 1) Interpersonal Communication is in good enough category (84%), 2) Employee performance is in good enough category (42%), 3) Influence of Interpersonal Communication on Employee Performance Daima Hotel Padang, with Asymp Sig for variable Interpersonal communication is 0.849 and for employee performance is 0.115. With the value of Sig> from 0.05, it means that the better communication interpersonal employees the better the results of employee performance in Daima Hotel Padang and vice versa. The effect of variable X to Y is 14.4%, while 85.6% is influenced by other factors such as work environment, work discipline, work motivation, and work atmosphere. It is recommended for the management of Daima Hotel Padang to foster the cohesiveness of employees in working and in communicating in order to achieve good performance.Kata kunci : Komunikasi Interpersonal, Kinerja